2013
DOI: 10.1136/emermed-2013-202965
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department malnutrition screening and support model improves outcomes in a pilot randomised controlled trial

Abstract: Objective To trial malnutrition screening in older adults presenting to an emergency department (ED) and compare two service delivery models of nutritional support on nutritional status, quality of life, falls and unplanned hospital admissions. Design Participants (>60 years) presenting to ED screened at malnutrition risk were randomly allocated to either the control group (receiving regular treatment from community hospital interface programme nursing staff ) or intervention group (receiving dietetic assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
(28 reference statements)
0
38
0
Order By: Relevance
“…Implementation of oral nutritional supplementation is inexpensive and may result in overall cost savings by accelerating recovery from illness and reducing readmissions. 49,50 A recent pilot study (N=19) has demonstrated the feasibility of an ED-based intervention to treat malnutrition in older adults; 21 further research is needed to characterize the costs and benefits of such a program and, if helpful, develop a scalable version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of oral nutritional supplementation is inexpensive and may result in overall cost savings by accelerating recovery from illness and reducing readmissions. 49,50 A recent pilot study (N=19) has demonstrated the feasibility of an ED-based intervention to treat malnutrition in older adults; 21 further research is needed to characterize the costs and benefits of such a program and, if helpful, develop a scalable version.…”
Section: Discussionmentioning
confidence: 99%
“…1518 Although there is growing awareness of the potential value of screening for health conditions among older adults in the ED, including non-medical conditions, malnutrition was not identified as a screening target in recently published guidelines. 19,20 A 2013 study in Australia demonstrated the feasibility of interventions to treat malnutrition among older ED patients, 21 but in order to determine the potential impact of such interventions, a better understanding of the epidemiology of malnutrition among older ED patients is needed. We sought to estimate the prevalence of malnutrition and risk for malnutrition among older adults presenting to a single ED and identify subgroups at increased risk.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the ED is a potentially important setting for identifying and addressing malnutrition. Prior research has found that the burden of malnutrition is high among older adults presenting to the ED, with prevalence point estimates ranging from 12% to 16% . Only one clinical trial has examined the value of identifying and treating malnutrition in older ED patients .…”
mentioning
confidence: 99%
“…5,8,9 Only one clinical trial has examined the value of identifying and treating malnutrition in older ED patients. 8 This pilot study provided patients with individualized dietary counseling over a period of 12 weeks and observed clinically important but non-statistically significant improvements in quality of life and reductions in healthcare utilization. Although these results support the need for a large trial, much remains unknown about the optimal strategy to improve nutritional health among malnourished older ED patients.…”
mentioning
confidence: 99%
“…<15 and < 17 kg/m 2 in females and males, respectively) (25). Malnutrition often remains unrecognized and hence untreated (9,20,(26)(27)(28). Clinical staff can miss malnutrition in older adults due to barriers that affect nutritional screening including a lack of routine nutritional screening in many hospitals (9,29), and a belief by clinical staff that individual judgement of nutritional status is more superior (30,31).…”
mentioning
confidence: 99%